1543. The More Resistant, the More Fatal: Results of 414 Bacteremia Episodes in Febril Neutropenic Patients. (26th November 2018) - Surme, Serkan; Ozdemir, Yusuf E; Sahin, Meryem; Balkan, Ilker I; Mete, Bilgul; Can, Gunay; Tabak, Fehmi; Saltoglu, Nese
Abstract: Background: The objective of this study was to investigate the features of antimicrobial resistance in the microorganisms isolated from blood cultures of cases with FN and the relationship between resistance and mortality rates. Methods: We conducted a single-centre retrospective surveillance study of hospitalized cases with FN who had bloodstream infection (BSI) between 2012 and 2016. Organisms were identified according to current conventional procedures. Results: We determined 414 episodes of BSI in 252 patients of whom 53.6% were male and median age was 50 years. Distribution of common microorganisms causing BSI is presented in Figure 1. Rates and patterns of resistant microorganisms are presented in Table 1 and Figure 2. Catheter-related bacteremia constituted 49.8% (206/414) of total episodes and 30-day mortality was significantly lower ( P < 0.007) in this group. In total, 30-day crude mortality rate was 14.7% (61/414 episodes). The mortality rates were 7.4, 18.6, 32.4 and 50% in BSI episodes due to Gram-positive, Gram-negative bacterial, polymicrobial and fungal etiology, respectively. Among Gram-negatives 30-day mortality was significantly associated with the presence of resistance; extended-spectrum β-lactamase (ESBL) ( P = 0.006), carbapenem resistance ( P < 0.0001), piperacillin/tazobactam resistance ( P < 0.0001) and colistin resistance ( P = 0.009). Among Gram-positives 30-day mortality was not associated with presence of resistance. Conclusion: The rate of carbapenem and colistin resistance has increased over the years. Changing antimicrobial resistance pattern particularly in Gram negatives is among the most decisive parameters for the success of empirical treatment and antimicrobial stewardship. Disclosures: All authors: No reported disclosures.